"Mechanization Takes Command?": Powered Machinery and Production Times in Late Nineteenth-Century American Manufacturing. (7th September 2022) - Atack, Jeremy; Margo, Robert A.; Rhode, Paul W.
Abstract : During the nineteenth century, U.S. manufacturers shifted away from the "hand labor" mode of production, characteristic of artisan shops, to "machine labor, " which was increasingly concentrated in steam-powered factories. This transition fundamentally changed production tasks, jobs, and job requirements. This paper uses digitized data on these two production modes from an 1899 U.S. Commissioner of Labor report to estimate the frequency and impact of the use of inanimate power on production operation times. About half of production operations were mechanized; the use of inanimate power raised productivity, accounting for about one-quarter to one-third of the overall productivity advantage of machine labor. However, additional factors, such as the increased division of labor and adoption of high-volume production, also played quantitatively important roles in raising productivity in machine production versus by hand.